Does Bilateral Pulmonary Banding in Comparison to Norwood Procedure Improve Outcome in Neonates with Hypoplastic Left Heart Syndrome Beyond Second-Stage Palliation? A Review of the Current Literature - Photiadis, Joachim; Sinzobahamvya, Nicodème; Hraška, Viktor; Asfour, Boulos (The Thoracic and Cardiovascular Surgeon, 2012)
Best evidence protocol was applied and the question addressed, whether there is an outcome advantage of a hybrid approach including bilateral pulmonary banding (BPB) and ductal stenting over Norwood procedure (NP) to maintain systemic circulation and to restrict pulmonary blood flow in neonates with hypoplastic left heart syndrome (HLHS). Out of 80 articles published since the original description of BPB in 2002, eight were selected to answer the clinical question. All studies were retrospective case-series after BLB, only three compared results with NP controls, but not in a randomized fashion. Only three chose high-risk patients. Mean follow-up interval was mentioned only in one study. Reported mean hospital, interstage, and stage 2 mortalities after BPB was 17.3, 12.4, and 25.3%, respectively. Estimated transplant-free survival beyond stage 2 palliation ranged from 7 to 80%, with no significant differences to NP controls in three studies. Reintervention rate was high, ranging from 20 to 42% at different sites. Due to study design or inhomogeneity of patient groups, current literature does not show evidence that bilateral pulmonary banding improves outcome with respect to survival beyond second-stage HLHS palliation.
Keywords: bilateral banding; hybrid; hypoplastic left heart; Norwood operation